2002
DOI: 10.1038/sj.bmt.1703522
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide as salvage therapy for VAD-refractory multiple myeloma prior to autologous PBSCT

Abstract: Summary:Several trials have shown the activity of thalidomide (THAL) in relapsed multiple myeloma (MM) patients failing PBSCT or conventional chemotherapy. PBSCT is considered standard treatment for most patients requiring therapy for MM; however, patients with VAD-resistant disease may not be able to receive PBSCT due to rapidly advancing disease. We report four cases of VAD-refractory MM salvaged with THAL ؉ VAD followed by PBSCT. All patients underwent stem cell mobilization with cyclophosphamide (Cy) (4.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The HOVON-50-data showed a median time to leukapheresis in TAD patients of 11 days (7-52) and 11 days (9-24) for VAD patients. In line with our results, Ghobrial et al 17 showed no difference between Thal and control group regarding the number of days of leukapheresis, but they remarked that patients from the Thal group were not likely to collect sufficiently in 1 day, similar to the group of Ahmad et al 18 who administered Thal continuously during leukapheresis. In contrast, Desikan et al 10 …”
Section: Pbsc Collectionsupporting
confidence: 80%
See 1 more Smart Citation
“…The HOVON-50-data showed a median time to leukapheresis in TAD patients of 11 days (7-52) and 11 days (9-24) for VAD patients. In line with our results, Ghobrial et al 17 showed no difference between Thal and control group regarding the number of days of leukapheresis, but they remarked that patients from the Thal group were not likely to collect sufficiently in 1 day, similar to the group of Ahmad et al 18 who administered Thal continuously during leukapheresis. In contrast, Desikan et al 10 …”
Section: Pbsc Collectionsupporting
confidence: 80%
“…Importantly, no difference was found in the recovery of WBC, ANC or PLT in either VAD or TAD after first ABSCT (Table 4). Similarly, Ahmad et al 18 showed that hematopoetic reconstitution (ANC40.5 Â 10 9 /l, PLT 420 Â 10 9 /l) occurred between 12 and 16 days after ABSCT, pretreated with VAD and Thal. We next investigated if an influence could be seen on the number of PLT or red blood cells (RBC) transfused during engraftment time, and no difference was found in both treatment groups.…”
Section: Hematopoetic Reconstitution After First Absctmentioning
confidence: 99%
“…Similar to other trials (27, 38, 39), our study shows that the combination of thalidomide with chemotherapy does not have a negative impact on mobilization and collection of PBSC, as found in the 20 patients who were candidates for autologous PBSCT. In the 17 of the 19 patients (89%) who actually received high‐dose chemotherapy with PBSCT, a normal recovery of peripheral blood cell counts was observed despite continuous treatment with thalidomide.…”
Section: Discussionsupporting
confidence: 88%
“…It has been confirmed by many study groups that THAL as a single agent (Dmoszynska et al, 2000;Patriarca et al, 2003) or combined with VAD (Ahmad et al, 2002;Pitini et al, 2003) could be a suitable bridging regimen to PBSC collection and autologous SCT for VAD-refractory MM patients. Moreover, Ghobrial et al (2003) showed that THAL does not substantionally affect peripheral blood mobilisation or engraftment, which is in line with our observation.…”
Section: Discussionmentioning
confidence: 96%